SIRT6 Through the Brain Evolution, Development, and Aging - Garcia-Venzor, Alfredo; Toiber, Debra (Frontiers in Aging Neuroscience, 2021)
During an organism’s lifespan, two main phenomena are critical for the organism’s survival. These are 1) a proper embryonic development, which permits the new organism to function with high fitness, grow and reproduce, and 2) the aging process, which will progressively undermine its competence and fitness for survival, leading to its death. Interestingly these processes present various similarities at the molecular level. Notably, as organisms became more complex, regulation of these processes became coordinated by the brain, and failure in brain activity is detrimental in both development and aging. One of the critical processes regulating brain health is the capacity to keep its genomic integrity and epigenetic regulation—deficiency in DNA repair results in neurodevelopmental and neurodegenerative diseases. As the brain becomes more complex, this effect becomes more evident. In this perspective, we will analyze how the brain evolved and became critical for human survival and the role SIRT6 plays in brain health. SIRT6 belongs to the Sirtuin family of histone deacetylases that control several cellular processes; among them, Sirt6 has been associated with the proper embryonic development and is associated with the aging process. In humans, Sirt6 has a pivotal role during brain aging, and its loss of function is correlated with the appearance of neurodegenerative diseases such as Alzheimer’s disease. However, Sirt6 roles during brain development and aging, especially the last one, are not observed in all species. It appears that during the brain organ evolution, Sirt6 has gained more relevance as the brain becomes bigger and more complex, observing the most detrimental effect in the brains of homo sapiens. In this perspective, we part from the evolution of the brain in metazoans, the biological similarities between brain development and aging, the relevant functions of Sirt6 in these similar phenomena to conclude with the evidence suggesting a more relevant role of Sirt6 gained in the brain evolution.